THE INFLUENCE OF CELEBRITY ENDORSEMENT, BRAND IMAGE, PRODUCT INNOVATION AND PRICE SUITABILITY ON PURCHASING INTEREST OF GENERATION Z CONSUMERS IN SCARLETT PRODUCTS (STUDY OF STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS MALIKUSSALEH UNIVERSITY USERS - Muhammad Whasil Mufti Ulwan; Rusydi; Adnan; T. Edyansyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
innovation and price suitability on generation Z consumers' buying interest in Scarlett products among students at the Faculty of Economics and Business at Malikussaleh University. The sample that will be used in this research is 105 consumers. The research method in this thesis uses quantitative methods with a descriptive approach. The data analysis tool used is multiple regression. The results of the research show that celebrity endorsement does not have a positive and significant effect on generation Z consumers' buying interest in Scarlett products among students at the Faculty of Economics and Business at Malikussaleh University, brand image has a positive and significant effect on Generation Z consumers' buying interest in Scarlett products among students at the Faculty of Economics and Business. Malikussaleh University, Product innovation does not have a positive and significant effect on generation Z consumers' buying interest in Scarlett products among students at the Faculty of Economics and Business at Malikussaleh University and price conformity has a positive and significant effect on Generation Z consumers' buying interest in Scarlett products among students at the University's Faculty of Economics and Business. Malikussaleh. Meanwhile, the results of simultaneous testing showed that Celebrity Endorsement (X1), Brand Image (X2), Product Innovation (X3) and Price Suitability (X4) had a significant effect on Generation Z consumers' buying interest (Y) in Scarlett products among students at the Faculty of Economics and Business. Malikussaleh university.